Pengaruh Harga, Kualitas Jasa, Dan Promosi Terhadap Kepuasan Pelanggan Laundry Dalam Perspektif Ekonomi Islam (Studi Kasus Pada Laundry Fitri) - Neny Apriani (Tamaddun Ummah (JTU), 2022)
The purpose of this study was to determine the effect of price, service quality and promotion on customer satisfaction in an Islamic economic perspective. If an expectation is not met according to their needs, it is possible that customers will look for other products and even drop the company's image. This study uses a quantitative method approach with the data used in this study is primary data, namely Cahaya Laundry Customer Satisfaction in Purnama Village. Data analysis using Multiple Linear Regression Analysis with the help of SPSS 21 software for Windows. The results showed that for the effect of price, quality of promotional services on customer satisfaction Jasa Cahaya Laundry, seen from the regression coefficient of 0.336 or 33.6%. This means 33.6%. of the dependent variable, customer satisfaction is influenced by the independent variable of service quality, while the remaining 66.4% is influenced by other variables, but the value is small.